Application of Safe Sex Behaviour in Female Sex Worker and Sexual Transmitted Infection - Rahayu, Esty Puji; Rizki, Lailatul Khusnul; Masita, Elly Dwi; Handayani, Nanik; Amalia, Rizki (International Journal of Psychosocial Rehabilitation, 2020)
The incidence of STIs in the form of inflammation or ulceration will increase the risk of entering HIV infection when having unprotected sex between someone who has been infected with an STI (Sexually Transmitted Infections) and their partner. Preventing and treating STIs and HIV can reduce the risk of sexual transmission, especially in at-risk populations such as sex workers and their customers. The research method used was descriptive analytic with a crossectional approach and the sampling technique was purposive sampling. Data about safe sex behavior was obtained using questionnaires and interviews, while STI examination was carried out by physical examination and laboratory examination. The laboratory tests performed were vaginal swabs (gram staining and gymsa) and serological examinations (rapid tests). Results of a study on 36 female sex workers, 61.1% of female sex workers did not apply safe sex so that the results of 11.1% STI examination were diagnosed with condyloma, 88.8% received positive results in gram stain and exercise tests, 16.6% were diagnosed with syphilis and 27.8% received reactive results on HIV testing. The application of safe sex to risk groups greatly influences the occurrence of STIs and increases the risk of transmission of STIs because it needs promotive and preventive efforts by health workers to prevent the spread of STIs more widely.